Preparation method of Cu8GeSe6-based thermoelectric crystal
By using the method of using vertical growth furnaces and high thermal guidance rates during the preparation of CU8Gese6 base thermal electrical crystals, CU8GESE6 base heating crystalline mechanical performance and low thermal conductivity have been solved. Low thermal guidance is suitable for thermoelectric applications of nearly ventricular temperature environment.
Patent Information
- Application Number
- CN202411966593.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, the mechanical properties of Cu8GeSe6-based thermoelectric crystals are poor, the processing performance is poor, and holes are easily generated when preparing large-sized crystals, resulting in low thermal conductivity.
采用垂直生长炉结合高热导率坩埚的方法,通过设有三个温区的垂直生长炉进行晶体生长,并在坩埚密封前充入惰性气体,控制气压和坩埚下降速度,以减少晶体内部的孔洞和 Temperature difference.
The mechanical strength of the CU8Gese6 base thermal electrical crystals has been improved, reducing the thermal conductivity perpendicular to the axial direction within the temperature range of 300 ~ 500 K, making it more suitable for applications in the temperature environment in the near -room temperature.
Smart Images

Figure CN119372762A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of crystal growth, and in particular to a Cu 8 Ge 6 Method for preparing thermoelectric crystal based on thermoelectric crystal. Background Art
[0002] Thermoelectric conversion technology is based on the Seebeck effect, Peltier effect and Thomson effect, and can realize the mutual conversion between electrical energy and thermal energy. It can be used to convert low-grade thermal energy into electrical energy and improve energy utilization efficiency. It is an energy conversion technology with broad development prospects. In thermoelectric conversion technology, the core of achieving energy conversion is thermoelectric materials. How to improve the performance of thermoelectric materials is the research focus of thermoelectric conversion technology.
[0003] Cu 8 Ge 6 Thermoelectric crystal is a new type of thermoelectric material, in which the presence of two independent structural units gives Cu 8 Ge 6 Very low lattice thermal conductivity: In the non-fast ion conductor phase, copper ions and [GeSe 6 The weak chemical bonds between the frameworks can introduce a large number of low-frequency optical phonons with anharmonic vibrations into the material, hindering the propagation of normal phonons; in the fast ion conductor phase, copper ions have a strong liquid-like effect, which can strongly scatter phonons and soften some transverse wave phonons. The extremely low thermal conductivity can make Cu 8 Ge 6 Thermoelectric crystals have high z value.
[0004] In the prior art, Cu 8 Ge 6 Thermoelectric crystals are prepared by melting-quenching-annealing-hot pressing sintering, such as the literature "Cu 8 Ge 6 -based thermoelectric materials with an argyrodite structure” (Jiang B, Qiu P, Eikeland E, et al. Cu 8 Ge 6-based thermoelectric materials with an argyrodite structure[J]. Journal of Materials Chemistry C, 2017, 5(4):943-952. DOI:10.1039 / c6tc05068a.). Due to Cu 8 Ge 6 The thermal conductivity of the basic thermoelectric crystal is very low. This method is likely to produce a large number of holes when making large-sized crystals, resulting in low mechanical strength of the crystals, easy breakage during processing, and poor processing performance. Summary of the invention
[0005] In order to solve the above technical problems, the Cu prepared by the existing method is 8 Ge 6 The mechanical properties of the basic thermoelectric crystal are poor. The present invention provides a Cu 8 Ge 6 The preparation method of the thermoelectric crystal can reduce the 8 Ge 6 The holes in the base thermoelectric crystal can improve its mechanical strength and also make the Cu 8 Ge 6 The base thermoelectric crystal has a lower thermal conductivity perpendicular to the axis in the temperature range of 300~500 K.
[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a Cu 8 Ge 6 The method for preparing a thermoelectric crystal comprises the following steps: S1: Melt the single elements to make Cu 8 Ge 6 Base multi-crystal; S2: Cu 8 Ge 6 The base crystal is placed on a thermal conductivity higher than 100 W·m -1 ·K -1 The crucible is placed in a vacuum-sealed vertical growth furnace; the vertical growth furnace is provided with temperature zones I, II and III with decreasing temperatures from top to bottom; S3: will be loaded with Cu 8 Ge 6 After the crucible of the polycrystalline base is melted in temperature zone I, it is moved down to temperature zone II for crystal growth, and then moved down to temperature zone III for annealing to obtain Cu 8 Ge 6 Based on thermoelectric crystals.
[0007] For Cu with low thermal conductivity 8 Ge 6 For thermoelectric crystals, the temperature inside the crystal tends to show a gradient distribution under the influence of the temperature field. The present invention uses a crucible with high thermal conductivity to help reduce the temperature difference between different areas inside the crystal, making it easier to nucleate and grow along the axial direction under the temperature gradient in the vertical growth furnace, which helps to discharge the internal micropores, so that the final Cu 8 Ge 6 The base thermoelectric crystal has fewer holes, which can give the Cu 8 Ge 6 The higher mechanical strength of the base thermoelectric crystal makes it less likely to break during processing, thus achieving better processing performance.
[0008] In addition, Cu 8 Ge 6 The thermal conductivity of the base thermoelectric crystal is affected by many factors, such as the internal pore structure of the crystal, grain orientation, U process of phonon collision, multi-phonon effect, intrinsic excitation, etc. 8 Ge 6 For a thermoelectric crystal, the temperature environment will affect its U process, multi-phonon effect and intrinsic excitation, so the ambient temperature will also have a complex effect on the thermal conductivity. The same operation may have completely opposite effects on the thermal conductivity of this thermoelectric crystal in different temperature ranges. These factors are intertwined and complicated, and some principles are still unexplained. Therefore, the effect of the preparation process on Cu 8 Ge 6 The influence of the thermal conductivity of the base thermoelectric crystal in a specific temperature range is poorly predictable, which brings great difficulty to the research. The team of the present invention found that the preparation method of the present invention, in addition to making Cu 8 Ge 6 In addition to reducing the number of holes in the base thermoelectric crystal, it can also reduce its thermal conductivity perpendicular to the axis in the temperature range of 300~500 K, which will help improve the Cu 8 Ge 6 The thermoelectric performance of the basic thermoelectric crystal in this temperature range makes it more suitable for some applications requiring low thermal conductivity in a near-room temperature environment.
[0009] Preferably, in step S2, the crucible is a SiC crucible or a graphite crucible.
[0010] Preferably, in step S3, the temperature of the temperature zone I is 1000-1150°C, and the holding time of the crucible in the temperature zone I is 12-20 h; the temperature in the temperature zone II decreases from top to bottom at a gradient of 15-20°C / cm, and the crucible stays at a position with a temperature of 850-1000°C in the temperature zone II for 100-120 h; the temperature of the temperature zone III is 700-850°C, and the holding time of the crucible in the temperature zone III is 20-24 h.
[0011] Preferably, in step S3, the speed at which the crucible descends from temperature zone I to temperature zone II is 0.3-0.5 mm / h.
[0012] Preferably, in step S3, the speed at which the crucible descends from temperature zone II to temperature zone III is 0.1-0.5 mm / h.
[0013] Preferably, in step S3, the vacuum sealing step comprises: evacuating the crucible and then filling it with an inert gas, repeating this process multiple times, and the last time the inert gas is filled until the pressure in the crucible is 4×10 -4 ~6×10 -4 Pa, and then sealed with flame.
[0014] When the crucible drops from temperature I to temperature zone II and from temperature zone II to temperature zone III, as well as the improper control of the gas pressure after the last inert gas filling before sealing, the obtained Cu 8 Ge 6 The thermal conductivity of the basic thermoelectric crystal is relatively large in the direction perpendicular to the axis in the temperature range of 300~500 K.
[0015] Preferably, in step S3, the Cu 8 Ge 6 The base thermoelectric crystal is Cu 8-x A x Ge 1-y B y Se 6-z C z crystal; in step S1, the Cu 8 Ge 6 Cu based polycrystalline 8-x A x Ge 1-y B y Se 6-z C z Polycrystalline; Cu 8-x A x Ge 1-y B y Se 6-z C zIn which, A is Ag and / or Au, B is Si and / or Sn, C is S and / or Te, 0≤x≤8, 0≤y≤1, 0≤z≤6.
[0016] Preferably, in step S1, the process of mixed melting of the single substances is carried out in a vertical melting furnace or a rocking furnace; in the rocking furnace, the rocking time is controlled to be 0.5-3 h, the preparation temperature is 950-1200°C, the heating rate is 4-10°C / min, and the rocking rate is 10-30 r / min.
[0017] Preferably, in step S2, the bottom of the crucible is conical, and the taper is 10° to 70°.
[0018] Preferably, in step S2, the length of the crucible is 5-50 cm, and the diameter of the cylindrical part is 8-100 mm.
[0019] Preferably, in step S3, the Cu 8 Ge 6 The diameter of the base thermoelectric crystal is 8~100 mm and the length is 1~100 mm.
[0020] In the second aspect, the present invention provides a zone melting method for reducing Cu 8 Ge 6 Based on the application of thermal conductivity of thermoelectric crystals at 300-500K, the Cu 8 Ge 6 The method for preparing the thermoelectric crystal comprises the following steps: S1: Melt the single elements to make Cu 8 Ge 6 Base multi-crystal; S2: Cu 8 Ge 6 The base crystal is placed on a thermal conductivity higher than 100 W·m -1 ·K -1 The crucible is placed in a vacuum-sealed vertical growth furnace; the vertical growth furnace is provided with temperature zones I, II and III with decreasing temperatures from top to bottom; S3: will be loaded with Cu 8 Ge 6 After the crucible of the polycrystalline base is melted in temperature zone I, it is moved down to temperature zone II for crystal growth, and then moved down to temperature zone III for annealing to obtain Cu 8 Ge 6 Based on thermoelectric crystals.
[0021] In a third aspect, the present invention provides a method for reducing Cu 8 Ge 6The method of thermal conductivity of the Cu-based thermoelectric crystal at 300-500K 8 Ge 6 The method for preparing the thermoelectric crystal comprises the following steps: S1: Melt the single elements to make Cu 8 Ge 6 Base multi-crystal; S2: Cu 8 Ge 6 The base crystal is placed on a thermal conductivity higher than 100 W·m -1 ·K -1 The crucible is placed in a vacuum-sealed vertical growth furnace; the vertical growth furnace is provided with temperature zones I, II and III with decreasing temperatures from top to bottom; S3: will be loaded with Cu 8 Ge 6 After the crucible of the polycrystalline base is melted in temperature zone I, it is moved down to temperature zone II for crystal growth, and then moved down to temperature zone III for annealing to obtain Cu 8 Ge 6 Based on thermoelectric crystals.
[0022] Compared with the prior art, the present invention has the following advantages: (1) The present invention is used to prepare Cu 8 Ge 6 In the process of thermoelectric crystals, a vertical growth furnace is used with a high thermal conductivity crucible to make the obtained Cu 8 Ge 6 The number of internal pores in the base thermoelectric crystal is reduced, thereby improving its mechanical strength, making it less likely to break during processing and achieving better processing performance.
[0023] (2) In the present invention, the Cu 2+ is prepared by the comprehensive design of ① using a vertical growth furnace with three temperature zones for crystal growth + ② the gas pressure after the last inert gas filling before the crucible is sealed + ③ the speed at which the crucible descends from temperature zone I to temperature zone II and from temperature zone II to temperature zone III. 8 Ge 6 The base thermoelectric crystal has a lower thermal conductivity perpendicular to the axis in the temperature range of 300~500 K, which will help to improve the Cu 8 Ge 6 Thermoelectric properties of the basic thermoelectric crystal within this temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The Cu prepared in Example 1 8 Ge 6 The appearance of a basic thermoelectric crystal.
[0025] Figure 2 The Cu prepared in Example 1 8 Ge 6 X-ray diffraction spectrum of the base thermoelectric crystal.
[0026] Figure 3 The Cu prepared in Comparative Example 2 8 Ge 6 Optical photograph of the fracture surface of a base thermoelectric crystal fragment.
[0027] Figure 4 The Cu prepared in Example 1 and Comparative Example 1 8 Ge 6 The relationship between the thermal conductivity of the base thermoelectric crystal perpendicular to the axis and the temperature. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the embodiments.
[0029] A Cu 8 Ge 6 The method for preparing a thermoelectric crystal comprises the following steps: S1: Melt the single elements to make Cu 8 Ge 6 Base multi-crystal; S2: Cu 8 Ge 6 The base crystal is placed on a thermal conductivity higher than 100 W·m -1 ·K -1 The crucible is placed in a vacuum-sealed vertical growth furnace; the vertical growth furnace is provided with temperature zones I, II and III with decreasing temperatures from top to bottom; S3: will be loaded with Cu 8 Ge 6 After the crucible of the polycrystalline base is melted in temperature zone I, it is moved down to temperature zone II for crystal growth, and then moved down to temperature zone III for annealing to obtain Cu 8 Ge 6 Based on thermoelectric crystals.
[0030] In some specific embodiments, in step S3, the Cu 8 Ge 6 The base thermoelectric crystal is Cu 8-x A x Ge 1-y B y Se 6- z C z crystal; in step S1, the Cu 8 Ge 6Cu based polycrystalline 8-x A x Ge 1-y B y Se 6-z C z Polycrystalline; Cu 8-x A x Ge 1-y B y Se 6- z C z In which, A is Ag and / or Au, B is Si and / or Sn, C is S and / or Te, 0≤x≤8, 0≤y≤1, 0≤z≤6.
[0031] In some specific embodiments, the process of step S1 specifically includes: placing the single substance in a quartz crucible, vacuum sealing it, and placing it in a vertical melting furnace or a rocking furnace for mixed melting to obtain Cu 8 Ge 6 Based polycrystalline; in the rocking furnace, the rocking time is controlled to be 0.5~3 h, the preparation temperature is 950~1200℃, the heating rate is 4~10℃ / min, and the rocking rate is 10~30r / min.
[0032] In some specific embodiments, in step S2, the crucible is a SiC crucible or a graphite crucible.
[0033] In some specific embodiments, in step S2, the bottom of the crucible is conical, and the taper is 10° to 70°; the length of the crucible is 5 to 50 cm, and the diameter of the cylindrical part is 8 to 100 mm.
[0034] In some specific embodiments, in step S3, the vacuum sealing step includes: evacuating the crucible to a pressure no higher than 10 -4 Pa, then fill with inert gas, repeat several times, and the last time fill with inert gas until the pressure in the crucible is 4×10 -4 ~6×10 -4 Pa, and then sealed with flame.
[0035] In some specific embodiments, in step S3, the temperature of the temperature zone I is 1000-1150°C, and the holding time of the crucible in the temperature zone I is 12-20 h; the temperature in the temperature zone II decreases from top to bottom at a gradient of 15-20°C / cm, and the crucible stays at a position with a temperature of 850-1000°C in the temperature zone II for 100-120 h; the temperature of the temperature zone III is 700-850°C, and the holding time of the crucible in the temperature zone III is 20-24 h; the speed at which the crucible descends from the temperature zone I to the temperature zone II is 0.3-0.5 mm / h, and the speed at which the crucible descends from the temperature zone II to the temperature zone III is 0.1-0.5 mm / h.
[0036] In some specific embodiments, in step S3, the Cu 8 Ge 6 The diameter of the base thermoelectric crystal is 8~100 mm and the length is 1~100 mm.
[0037] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0038] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0039] Example 1 The Cu 8 Ge 6 Base Thermoelectric Crystal: S1: Preparation of Cu 8 Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity (purity 99.999%) Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 1100°C and kept at this temperature for 1 hour. During this time, the crucible is swung at a speed of 20 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0040] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. The vertical length of temperature zone I is 20 cm, and the temperature is set to 1150°C; the vertical length of temperature zone II is 10 cm, and the temperature is set to decrease from top to bottom at a gradient of 15°C / cm; the vertical length of temperature zone III is 20 cm, and the temperature is set to 700°C.
[0041] Take the Cu prepared in step S1 8 Ge 6 The polycrystal was placed in a graphite crucible. The bottom of the graphite crucible was conical with a taper of 60°. The diameter of the cylindrical part was 15 mm. The total length of the cylindrical part and the conical part was 10 cm. The graphite crucible was evacuated to a pressure of 10 -4 Pa, and then fill with argon gas, repeat this process 3 times, and the last time, fill with argon gas to a pressure of 5×10 - 4 Pa, and then sealed using an oxyhydrogen flame.
[0042] The sealed graphite crucible was placed in a vertical growth furnace and kept in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 0.5 mm / h, and the crucible was moved down to temperature zone II. It was kept at a set temperature of 950°C for 120 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 0.1 mm / h, and the crucible was moved down to the middle of temperature zone III. It was kept for 20 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 crystal).
[0043] The Cu prepared in this example 8 Ge 6 The appearance of the base thermoelectric crystal is as follows Figure 1 As shown, it consists of two parts, a cone and a cylinder, with a total length of 6 cm, a taper of the cone of 60°, and a diameter of the cylinder of 17 mm.
[0044] The Cu prepared in this example 8 Ge 6 The X-ray diffraction spectrum of the thermoelectric crystal is shown in Figure 2 As shown, Figure 2 This indicates that the crystal obtained in this example is single-phase.
[0045] Example 2 The Cu 8 Ge 6 Base Thermoelectric Crystal: S1: Preparation of Cu 8 Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 1100°C and kept at this temperature for 1 hour. During this time, the crucible is swung at a speed of 30 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0046] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. The vertical length of temperature zone I is 20 cm, and the temperature is set to 1000°C; the vertical length of temperature zone II is 15 cm, and the temperature is set to decrease from top to bottom at a gradient of 20°C / cm; the vertical length of temperature zone III is 10 cm, and the temperature is set to 750°C.
[0047] Take the Cu prepared in step S1 8 Ge 6 The polycrystal was placed in a graphite crucible. The bottom of the graphite crucible was conical with a taper of 10°. The diameter of the cylindrical part was 8 mm. The total length of the cylindrical part and the conical part was 15 cm. The graphite crucible was evacuated to a pressure of 10 -4 Pa, and then fill with argon gas, repeat this process 3 times, and the last time, fill with argon gas to a pressure of 6×10 -4 Pa, and then sealed using an oxyhydrogen flame.
[0048] The sealed graphite crucible was placed in a vertical growth furnace and kept in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 0.5 mm / h, and the crucible was moved down to temperature zone II. It was kept at a set temperature of 850°C for 110 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 0.5 mm / h, and the crucible was moved down to the middle of temperature zone III. It was kept for 24 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 Crystal), which consists of a cone and a cylinder, with a total length of 10 cm, a taper of 60° for the cone and a diameter of 8 mm for the cylinder.
[0049] Example 3 The Cu 8 Ge 6 Base Thermoelectric Crystal: S1: Preparation of Cu 8 Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 950 °C and kept at this temperature for 3 hours. During this time, the crucible is swung at a speed of 10 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0050] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. Temperature zone I is 20 cm long in the vertical direction and the temperature is set to 1150°C; temperature zone II is 15 cm long in the vertical direction and the temperature is set to decrease from top to bottom at a gradient of 15°C / cm; temperature zone III is 10 cm long in the vertical direction and the temperature is set to 850°C.
[0051] Take the Cu prepared in step S1 8 Ge 6The polycrystal was placed in a graphite crucible. The bottom of the graphite crucible was conical with a taper of 70°. The diameter of the cylindrical part was 100 mm. The total length of the cylindrical part and the conical part was 50 cm. The graphite crucible was evacuated to a pressure of 10 -4 Pa, and then fill with argon gas, repeat this process 3 times, and the last time, fill with argon gas to a pressure of 5×10 - 4 Pa, and then sealed using an oxyhydrogen flame.
[0052] The sealed graphite crucible was placed in a vertical growth furnace and kept in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 0.3 mm / h, and the crucible was moved down to temperature zone II. It was kept at a set temperature of 1000°C for 100 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 0.3 mm / h, and the crucible was moved down to the middle of temperature zone III. It was kept for 20 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 Crystal), which consists of a cone and a cylinder, with a total length of 12 cm, a taper of 60° for the cone and a diameter of 100 mm for the cylinder.
[0053] Comparative Example 1 This comparative example adopts the literature "Cu 8 Ge 6 -based thermoelectric materials with anargyrodite structure" was used to prepare Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 crystal).
[0054] Comparative Example 2 This comparative example prepared Cu according to the method in Example 1 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 The only difference from Example 1 is that in step S2, the graphite crucible is replaced with a quartz crucible. The rest of the process is the same as that of Example 1.
[0055] Specifically, this comparative example prepared Cu 8 Ge 6 The steps for making a thermoelectric crystal are as follows: S1: Preparation of Cu8 Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity (purity 99.999%) Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 1100°C and kept at this temperature for 1 hour. During this time, the crucible is swung at a speed of 20 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0056] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. The vertical length of temperature zone I is 20 cm, and the temperature is set to 1150°C; the vertical length of temperature zone II is 10 cm, and the temperature is set to decrease from top to bottom at a gradient of 15°C / cm; the vertical length of temperature zone III is 20 cm, and the temperature is set to 700°C.
[0057] Take the Cu prepared in step S1 8 Ge 6 The polycrystal was placed in a quartz crucible. The bottom of the quartz crucible was conical with a taper of 60°. The diameter of the cylindrical part was 15 mm. The total length of the cylindrical part and the conical part was 10 cm. The quartz crucible was evacuated to a pressure of 10 -4 Pa, and then fill with argon gas, repeat this process 3 times, and the last time, fill with argon gas to a pressure of 5×10 - 4 Pa, and then sealed using an oxyhydrogen flame.
[0058] The sealed quartz crucible was placed in a vertical growth furnace and kept in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 0.5 mm / h, and the crucible was moved down to temperature zone II. It was kept at a set temperature of 950°C for 120 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 0.1 mm / h, and the crucible was moved down to the middle of temperature zone III. It was kept for 20 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 crystal).
[0059] Comparative Example 3 This comparative example prepared Cu according to the method in Example 1 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 Crystal), the only difference from Example 1 is that: in step S2, before the graphite crucible is sealed with a hydrogen-oxygen flame, the last argon filling is performed to a pressure of 10 -3 The rest of the process is the same as in Example 1.
[0060] Specifically, the steps for preparing the Cu8GeSe6-based thermoelectric crystal in this comparative example are as follows: S1: Preparation of Cu 8 Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity (purity 99.999%) Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 1100°C and kept at this temperature for 1 hour. During this time, the crucible is swung at a speed of 20 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0061] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. The vertical length of temperature zone I is 20 cm, and the temperature is set to 1150°C; the vertical length of temperature zone II is 10 cm, and the temperature is set to decrease from top to bottom at a gradient of 15°C / cm; the vertical length of temperature zone III is 20 cm, and the temperature is set to 700°C.
[0062] Take the Cu prepared in step S1 8 Ge 6 The polycrystal was placed in a graphite crucible. The bottom of the graphite crucible was conical with a taper of 60°. The diameter of the cylindrical part was 15 mm. The total length of the cylindrical part and the conical part was 10 cm. The graphite crucible was evacuated to a pressure of 10 -4 Pa, then fill with argon gas, repeat this process 3 times, and fill with argon gas to a pressure of 10 -3 Pa, and then sealed using an oxyhydrogen flame.
[0063] The sealed graphite crucible was placed in a vertical growth furnace and kept in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 0.5 mm / h, and the crucible was moved down to temperature zone II. It was kept at a set temperature of 950°C for 120 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 0.1 mm / h, and the crucible was moved down to the middle of temperature zone III. It was kept for 20 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 Crystal), which consists of a cone and a cylinder, with a total length of 6 cm, a taper of 60° for the cone and a diameter of 17 mm for the cylinder.
[0064] Comparative Example 4 This comparative example prepared Cu according to the method in Example 1 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 Crystal), the only difference from Example 1 is that: in step S2, before the graphite crucible is sealed with a hydrogen-oxygen flame, no argon is filled after the last vacuuming (i.e., the gas pressure is 10 -4 The rest of the process is the same as in Example 1.
[0065] Specifically, the steps for preparing the Cu8GeSe6-based thermoelectric crystal in this comparative example are as follows: S1: Preparation of Cu 8 Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity (purity 99.999%) Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 1100°C and kept at this temperature for 1 hour. During this time, the crucible is swung at a speed of 20 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0066] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. The vertical length of temperature zone I is 20 cm, and the temperature is set to 1150°C; the vertical length of temperature zone II is 10 cm, and the temperature is set to decrease from top to bottom at a gradient of 15°C / cm; the vertical length of temperature zone III is 20 cm, and the temperature is set to 700°C.
[0067] Take the Cu prepared in step S1 8 Ge 6 The polycrystal was placed in a graphite crucible. The bottom of the graphite crucible was conical with a taper of 60°. The diameter of the cylindrical part was 15 mm. The total length of the cylindrical part and the conical part was 10 cm. The graphite crucible was evacuated to a pressure of 10 -4 Pa, then fill with argon, repeat 3 times, and finally evacuate to a pressure of 10 -4 After Pa, argon is not filled and then sealed using a hydrogen-oxygen flame.
[0068] The sealed graphite crucible was placed in a vertical growth furnace and kept in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 0.5 mm / h, and the crucible was moved down to temperature zone II. It was kept at a set temperature of 950°C for 120 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 0.1 mm / h, and the crucible was moved down to the middle of temperature zone III. It was kept for 20 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 Crystal), which consists of a cone and a cylinder, with a total length of 6 cm, a taper of 60° for the cone and a diameter of 17 mm for the cylinder.
[0069] Comparative Example 5 This comparative example prepared Cu according to the method in Example 1 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6 The only difference from Example 1 is that in step S2, the speed at which the crucible drops from temperature I to temperature zone II and from temperature zone II to temperature zone III is 1 mm / h. The rest of the process is the same as that of Example 1.
[0070] Specifically, the steps for preparing the Cu8GeSe6-based thermoelectric crystal in this comparative example are as follows: S1: Preparation of Cu 8Ge 6 Polycrystalline According to the stoichiometric ratio of 8:1:6, high-purity (purity 99.999%) Cu particles, Ge particles and Se particles were weighed and placed in a quartz crucible, and the vacuum was evacuated to a pressure of 10 -4 After the quartz crucible is sealed, the temperature is raised to 1100°C and kept at this temperature for 1 hour. During this time, the crucible is swung at a speed of 20 r / min to completely melt the raw materials and fully mix and react to obtain Cu 8 Ge 6 Polycrystalline.
[0071] S2: Preparation of Cu 8 Ge 6 Thermoelectric crystal The vertical growth furnace used in this step is provided with temperature zone I (high temperature zone), temperature zone II (medium temperature zone) and temperature zone III (low temperature zone) from top to bottom, with the temperature decreasing in sequence. The vertical length of temperature zone I is 20 cm, and the temperature is set to 1150°C; the vertical length of temperature zone II is 10 cm, and the temperature is set to decrease from top to bottom at a gradient of 15°C / cm; the vertical length of temperature zone III is 20 cm, and the temperature is set to 700°C.
[0072] Take the Cu prepared in step S1 8 Ge 6 The polycrystal was placed in a graphite crucible. The bottom of the graphite crucible was conical with a taper of 60°. The diameter of the cylindrical part was 15 mm. The total length of the cylindrical part and the conical part was 10 cm. The graphite crucible was evacuated to a pressure of 10 -4 Pa, and then fill with argon gas, repeat this process 3 times, and the last time, fill with argon gas to a pressure of 5×10 - 4 Pa, and then sealed using an oxyhydrogen flame.
[0073] The sealed graphite crucible was placed in a vertical growth furnace and stayed in the middle of temperature zone I for 20 hours to allow the polycrystal to melt and the solid-liquid interface to stabilize. Then the lifting device was started, the descent speed was set to 1 mm / h, and the crucible was moved down to temperature zone II. It stayed at a set temperature of 950°C for 120 hours to allow the crystal to grow until all the melt was crystallized. The lifting device was started again, the descent speed was set to 1 mm / h, and the crucible was moved down to the middle of temperature zone III. It stayed for 20 hours to complete annealing. Finally, it was cooled to room temperature to obtain Cu 8 Ge 6 Based thermoelectric crystal (Cu 8 Ge 6Crystal), which consists of a cone and a cylinder, with a total length of 6 cm, a taper of 60° for the cone and a diameter of 17 mm for the cylinder.
[0074] Test Case Take the Cu prepared in each embodiment and comparative example 8 Ge 6 Based on the thermoelectric crystal, its porosity, mechanical strength and thermal conductivity perpendicular to the axis at different temperatures (unit: W·K -1 ·m -1 ) were tested, and the results are shown in Tables 1 and 2. The mechanical strength was tested by vacuuming, and the test pressure was 10 -4 Pa and 10 -3 Pa, in Comparative Example 2, "5×10 -3 Pa pressure crushing" refers to Cu 8 Ge 6 The base thermoelectric crystal was broken during the preparation process. The optical photograph of its fracture is as follows: Figure 3 shown.
[0075] Table 1 Cu 8 Ge 6 Porosity and mechanical strength test results of the thermoelectric crystal
[0076] Table 2 Cu 8 Ge 6 Thermal conductivity test results of the thermoelectric crystal (thermal conductivity unit: W·K -1 ·m -1 )
[0077] By analyzing the test results in Table 1 and Table 2, we can see that: (1) By using the method of the present invention, combined with reasonable crystal growth process parameter design, a complete Cu with large size and low thermal conductivity at 300-500 K can be obtained. 8 Ge 6 Based on thermoelectric crystals.
[0078] (2) Cu prepared in Comparative Example 1 8 Ge 6 The crystal is placed in a relatively low vacuum (pressure 10 -3 Pa) and the Cu prepared in Example 1 8 Ge 6 The crystal is in a high vacuum (pressure 10 -4Pa), indicating that the latter has higher mechanical strength, and the porosity of the crystals obtained in Example 1 is lower than that in Comparative Example 1. The reason for this is that compared with the melting-quenching-annealing-hot pressing sintering method in the prior art, the method of the present invention is more likely to nucleate and grow along the axial direction, which is conducive to the discharge of internal micropores, so that the Cu 8 Ge 6 The base thermoelectric crystal has fewer holes.
[0079] (3) Compared with Comparative Example 2, the crystals obtained in Example 1 have lower porosity and higher mechanical strength. The reason for this is that for Cu with low thermal conductivity 8 Ge 6 For thermoelectric crystals, the temperature inside the crystal tends to show a gradient distribution under the influence of the temperature field. The present invention uses a crucible with high thermal conductivity to help reduce the temperature difference between different areas inside the crystal, making it easier to nucleate and grow along the axial direction under the temperature gradient in the vertical growth furnace, thereby reducing the Cu 8 Ge 6 Holes in the base thermoelectric crystal.
[0080] (4) Comparing the thermal conductivity test results of Example 1 and Comparative Example 1, it can be seen that: at a temperature of 300-500 K, the thermal conductivity of the crystal prepared in Example 1 in the direction perpendicular to the axis is lower than that of Comparative Example 1 (in order to more intuitively show the difference in thermal conductivity between the two, the relationship between the thermal conductivity of Example 1 and Comparative Example 1 and the temperature is shown in the figure below). Figure 4 The above results show that compared with the melting-quenching-annealing-hot pressing sintering method in the prior art, the method of the present invention can make the Cu 8 Ge 6 The thermal conductivity of the base thermoelectric crystal perpendicular to the axis decreases at a temperature of 300-500 K.
[0081] (5) Compared with Comparative Examples 3 to 5, the thermal conductivity of the crystal obtained in Example 1 is higher in the perpendicular direction to the axis at 300 to 500 K. The above results show that when the speed of the crucible dropping from temperature I to temperature zone II and from temperature zone II to temperature zone III, as well as the improper control of the gas pressure after the last inert gas filling before sealing, the obtained Cu 8 Ge 6 The thermal conductivity of the basic thermoelectric crystal is relatively large in the direction perpendicular to the axis in the temperature range of 300~500 K.
[0082] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a Cu8GeSe6-based thermoelectric crystal, characterized in that: The following steps are involved: S1: Mix and melt the single substances to form Cu8GeSe6-based polycrystals; S2: Place the Cu8GeSe6-based polycrystal in a thermal conductivity higher than 100 W·m -1 ·K -1 The crucible is placed in a vacuum-sealed vertical growth furnace; the vertical growth furnace is provided with temperature zones I, II and III with decreasing temperatures from top to bottom; S3: After melting the crystal in the crucible containing the Cu8GeSe6-based polycrystal in temperature zone I, the crucible is moved down to temperature zone II for crystal growth, and then moved down to temperature zone III for annealing to obtain a Cu8GeSe6-based thermoelectric crystal.
2. The preparation method according to claim 1, characterized in that: In step S2, the crucible is a SiC crucible or a graphite crucible.
3. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the temperature zone I is 1000-1150°C, and the holding time of the crucible in the temperature zone I is 12-20 h; the temperature in the temperature zone II decreases from top to bottom at a gradient of 15-20°C / cm, and the crucible stays at a position with a temperature of 850-1000°C in the temperature zone II for 100-120 h; the temperature of the temperature zone III is 600-850°C, and the holding time of the crucible in the temperature zone III is 20-24 h.
4. The preparation method according to claim 1 or 2, characterized in that: In step S3, the speed at which the crucible descends from temperature zone I to temperature zone II is 0.3-0.5 mm / h.
5. The preparation method according to claim 1 or 2, characterized in that: In step S3, the speed at which the crucible descends from temperature zone II to temperature zone III is 0.1-0.5 mm / h.
6. The preparation method according to claim 1, characterized in that: In step S3, the vacuum sealing step includes: evacuating the crucible and then filling it with an inert gas, repeating this process multiple times, and the last time the inert gas is filled until the pressure in the crucible is 4×10 -4 ~6×10 -4 Pa, and then sealed with flame.
7. The preparation method according to claim 1, characterized in that: In step S3, the Cu8GeSe6-based thermoelectric crystal is Cu 8-x A x Ge 1-y B y Se 6-z C z In step S1, the Cu8GeSe6-based polycrystalline is Cu 8-x A x Ge 1-y B y Se 6-z C z Polycrystalline; Cu 8-x A x Ge 1-y B y Se 6-z C z In which, A is Ag and / or Au, B is Si and / or Sn, C is S and / or Te, 0≤x≤8, 0≤y≤1, 0≤z≤6.
8. The preparation method according to claim 1, characterized in that: In step S1, the process of mixing and melting the single substances is carried out in a vertical melting furnace or a swinging furnace; in the swinging furnace, the swinging time is controlled to be 0.5-3 h, the preparation temperature is 950-1200°C, the heating rate is 4-10°C / min, and the swing rate is 10-30 r / min.
9. The preparation method according to claim 1, characterized in that: In step S2, the bottom of the crucible is conical, and the taper is 10° to 70°.
10. The preparation method according to claim 1, characterized in that: In step S2, the length of the crucible is 5-50 cm, and the diameter of the cylindrical part is 8-100 mm.
Citation Information
Patent Citations
Polycrystalline SnSe2 low-cost thermoelectric material and preparation method thereof
CN108396387A
Ag8SnSe6 crystal growth method
CN108588841A
Crystal growth device and preparation method of relaxor ferroelectric single crystal material
CN114892260A
Crystal growth device with crucible descending visual inoculation and method thereof
CN115896921A
Preparation method of quaternary copper-based diamond-like semiconductor crystal
CN117385473A